Behavioral and histological analyses of the mouse Bassoon p.P3882A mutation corresponding to the human BSN p.P3866A mutation - Tanaka, Daiki; Yaguchi, Hiroaki; Yoshizaki, Kaichi; Kudo, Akihiko; Mori, Fumiaki; Nomura, Taichi; Pan, Jing; Miki, Yasuo; Takahashi, Hidehisa; Hara, Taichi; Wakabayashi, Koichi; Yabe, Ichiro (Frontiers in Neuroscience, 2024)
Tauopathy is known to be a major pathognomonic finding in important neurodegenerative diseases such as progressive supranuclear palsy (PSP) and corticobasal degeneration. However, the mechanism by which tauopathy is triggered remains to be elucidated. We previously identified the point mutation c.11596C > G, p.Pro3866Ala in the Bassoon gene (BSN) in a Japanese family with PSP-like syndrome. We showed that mutated BSN may have been involved in its own insolubilization and tau accumulation. Furthermore, BSN mutations have also been related to various neurological diseases. In order to further investigate the pathophysiology of BSN mutation in detail, it is essential to study it in mouse models. We generated a mouse model with the mouse Bassoon p.P3882A mutation, which corresponds to the human BSN p.P3866A mutation, knock-in (KI) and we performed systematic behavioral and histological analyses. Behavioral analyses revealed impaired working memory in a Y-maze test at 3 months of age and decreased locomotor activity in the home cage at 3 and 12 months of age in KI mice compared to those in wild-type mice. Although no obvious structural abnormalities were observed at 3 months of age, immunohistochemical studies showed elevation of Bsn immunoreactivity in the hippocampus and neuronal loss without tau accumulation in the substantia nigra at 12 months of age in KI mice. Although our mice model did not show progressive cognitive dysfunction and locomotor disorder like PSP-like syndrome, dopaminergic neuronal loss was observed in the substantia nigra in 12-month-old KI mice. It is possible that BSN mutation may result in dopaminergic neuronal loss without locomotor symptoms due to the early disease stage. Thus, further clinical course can induce cognitive dysfunction and locomotor symptoms.